C / SiOx composite shell-coated lithium battery negative electrode material and preparation method thereof
By using mechanochemical method to develop the C/SiOx composite shell on the negative electrode material of lithium-ion battery, the battery capacity attenuation caused by low conductivity and volume changes in silicon negative electrode materials is solved, and a lithium-ion negative electrode material with high conductivity, mechanical toughness and long life is achieved.
Patent Information
- Application Number
- CN202411989208.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
The existing lithium-ion battery negative electrode material silicon has a fast attenuation of battery capacity due to low conductivity and large volume changes during lithium ion deintercalation. The traditional carbon cladding layer is prone to cracking under expansion stress, while the oxide cladding layer with poor conductivity limits the degree of lithiation.
The lithium battery negative electrode material Si@C/SiOx coated with C/SiOx composite shell was developed by mechanochemical method. Through the interlaced arrangement of the C phase and the SiOx phase, a composite shell with high conductivity, excellent lithium ion transport capability and strong mechanical toughness was formed.
It significantly improves the structural stability and interface stability of the silicon negative electrode, extends the service life of the battery, and improves the density and energy density of the negative electrode material during the electrochemical cycle.
Smart Images

Figure CN119764415A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries and particularly relates to a C / SiO x Composite shell-coated lithium battery negative electrode material and preparation method thereof. Background Art
[0002] Under the guidance of the new round of scientific and technological revolution and the "dual carbon" goal, energy storage devices represented by lithium-ion power batteries have developed rapidly. At present, the negative electrode material of commercial lithium-ion batteries is mainly graphite, but the theoretical specific capacity of graphite is only 372mAh g -1 , which is far from meeting the high energy density requirements of lithium-ion batteries in the new energy vehicle industry. Silicon is abundant in the earth's crust. When used as a negative electrode material for lithium-ion batteries, its charge and discharge voltage is low. At the same time, its theoretical specific capacity is nearly 10 times that of graphite (3579mAh g -1 ), is an ideal negative electrode material for improving the energy density of lithium-ion batteries. However, there are still many key issues to be solved in using silicon as an electrode material, such as the low electrical conductivity of silicon (3×10 -5 S cm -1 ), and there is a large volume change (~300%) during the process of silicon intercalation and deintercalation of lithium ions, which causes the pulverization of silicon particles and the instability of the solid electrolyte film (SEI) on the surface of the silicon negative electrode during charging and discharging, thereby leading to a sharp decay of battery capacity.
[0003] The surface coating of silicon can not only buffer the volume expansion of silicon during lithiation, but also improve the x The compactness of Si alloys, and the coating layer provides a stable silicon surface, which reduces the impact of silicon volume effect on the solid electrolyte film on the surface of the silicon negative electrode, and is an important means to improve the electrochemical performance of the silicon negative electrode. Carbon materials have high conductivity and structural stability. When used as coating layers, they can effectively improve the rate performance and cycle life of silicon negative electrodes. They are the most common coating materials (Advanced Functional Materials, 2018, 28: 1800855; New Carbon Materials, 2022, 37 (1): 245-258). However, the plasticity of carbon materials is poor, and they are prone to cracking under the repeated action of expansion stress, resulting in the failure of the carbon coating. Other coating materials such as TiO2, Al2O3, SiO xSuch coatings have high mechanical strength and can significantly improve the cycle stability of silicon negative electrodes, but the conductivity of such coatings is poor, and when the coating is too thick, it will limit the degree of lithiation of silicon, resulting in a decrease in the capacity of the silicon negative electrode (Advanced Energy Materials, 2018, 8: 1801718; Advanced Materials, 2017, 29: 1700523). Therefore, by designing the structure and composition of the coating, constructing a silicon coating with good conductivity and high mechanical properties is an effective way to improve the performance of lithium-ion battery negative electrodes.
[0004] This scheme proposes a C / SiO x The composite shell-coated lithium battery negative electrode material and the preparation method thereof are used to solve the above-mentioned technical problems. Summary of the invention
[0005] The object of the present invention is to provide a C / SiO x The composite shell-coated lithium battery negative electrode material and its preparation method overcome the difficulty of achieving both high conductivity and high toughness in the traditional silicon-coated shell, and improve the structural stability and interface stability of the silicon negative electrode. x New lithium battery negative electrode material (Si@C / SiO x ), in Si@C / SiO x In the coating shell, C phase and SiO x The staggered arrangement makes C / SiO x The composite shell has high electronic conductivity, excellent lithium ion transmission ability and strong mechanical toughness, which can significantly improve the structural integrity and electrochemical performance of the silicon negative electrode.
[0006] The technical purpose of the present invention is achieved by the following steps:
[0007] A C / SiO x Composite shell-coated lithium battery negative electrode material, with silicon as the core and C / SiO x For composite shell, C / SiO x The composite shell is evenly coated on the silicon surface, and the C / SiO x C phase and SiO in the composite shell x Staggered arrangement.
[0008] Si@C / SiO x The morphology is that small particles are assembled into large spheres with a diameter of 5-20 μm.
[0009] A C / SiO x The method for preparing a composite shell-coated lithium battery negative electrode material specifically comprises the following steps:
[0010] Step S1: uniformly dispersing the carbon source material in a solvent to obtain a carbon source material solution;
[0011] Step S2: adding nano-silicon to the carbon source material solution obtained in step S1, stirring in a water bath until the solvent is completely volatilized, and then placing it in a vacuum oven to dry, to obtain nano-silicon coated with the carbon source material;
[0012] Step S3: mechanically ball milling the nano-silicon coated with the carbon source material obtained in step S2;
[0013] Step S4: The sample obtained after ball milling in step S3 is subjected to high temperature carbonization treatment under an inert atmosphere to obtain C / SiO x Composite shell-coated lithium battery negative electrode material, denoted as Si@C / SiO x .
[0014] In the step S1, the carbon source material is one or a combination of organic polymers such as chitosan, asphalt, and resin;
[0015] The solvent is any one of deionized water, dilute acetic acid solution, methanol, ethanol, and N-methylpyrrolidone, or a combination of several of them;
[0016] The dispersion method is any one of ultrasound, shear homogenization dispersion and mechanical stirring or a combination of these, and the concentration of the carbon source material solution is 0.5-10 mg mL -1 .
[0017] In the step S2, the mass ratio of the nano-silicon to the carbon source material is 10:(0.1-5), the water bath temperature is 50-90° C., the temperature in the vacuum oven is 80-120° C., and the drying time is 5-30 hours.
[0018] In the step S3, the mechanical ball milling parameters are: ball-to-material mass ratio is (8-12):1, ball mill speed is 200-1200 rpm, and ball milling time is 2-24 h.
[0019] In step S4, the protective atmosphere refers to any one of nitrogen and argon or a combination of them, and the high-temperature carbonization temperature range is 400-1600° C., and the high-temperature carbonization time is 0.5-10 h.
[0020] The present invention mainly has the following beneficial effects:
[0021] (1) The present invention develops a C / SiO x Composite shell-coated lithium battery anode material Si@C / SiO x , the obtained C / SiO x The composite shell is a continuous layer of C phase and SiOx The interlocking and alternately arranged structure not only has high electronic conductivity, but also has high mechanical toughness, which can not only improve the electron transport and ion transfer capabilities of the lithium battery negative electrode, but also improve the structural stability of the negative electrode material during the electrochemical cycle;
[0022] (2) Si@C / SiO developed by the present invention x , by adding SiO x The introduction of LiF phase into the coating shell can achieve the regulation of the SEI film components on the negative electrode surface, generate a highly stable SEI film rich in LiF, avoid the continuous consumption of electrolyte during the electrochemical cycle, and thus improve the service life of the lithium battery negative electrode;
[0023] (3) Si@C / SiO developed by the present invention x It presents a morphology of small particles assembled into large spheres with a diameter of 5-20μm. Compared with nano-silicon, the density has been greatly improved, which is helpful to construct a high-area capacity lithium battery negative electrode and has good commercial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1a The Si@C / SiO x Scanning electron microscope photos of
[0025] Figure 1b The Si@C / SiO x Dark field scanning transmission electron microscopy image (inset: corresponding line scan element distribution map);
[0026] Figure 2 The graphs are the cycle performances of the lithium ion batteries in Example 1 and Comparative Example 1 of the present invention at a current density of 1 A / g;
[0027] Figure 3a The LiF and LiPO in the SEI film of Example 1 after different cycles obtained by X-ray photoelectron spectroscopy in the present invention. y F x / Li x PF y Content;
[0028] Figure 3b The LiF and LiPO in the SEI film of Comparative Example 1 are obtained by X-ray photoelectron spectroscopy in the present invention and after different cycles. y F x / Li x PF y The content. DETAILED DESCRIPTION
[0029] In order to more clearly illustrate the technical features of this solution, this solution is described below through specific implementation methods.
[0030] Example 1
[0031] Chitosan was used as the carbon source to prepare C / SiO x The preparation method of the composite shell-coated lithium battery negative electrode material comprises the following steps:
[0032] (1) Add 60 mg of chitosan to 30 mL of 5% dilute acetic acid solution and stir in a 50°C water bath for 5 hours to obtain a concentration of 2 mg mL -1 Chitosan solution;
[0033] (2) adding 200 mg of nano-silicon to 10 mL of the chitosan solution obtained in step (1), stirring in a 70° C. water bath until the solvent is completely evaporated, and then drying in a vacuum oven at 100° C. for 24 h to obtain chitosan-coated nano-silicon;
[0034] (3) mechanically ball milling the chitosan-coated nano-silicon obtained in step (2) at a speed of 450 rpm for 2 h;
[0035] (4) The sample obtained in step (3) was placed in a nitrogen atmosphere and carbonized at 900°C for 2 hours to obtain C / SiO x Composite shell-coated lithium battery anode material Si@C / SiO x .
[0036] like Figure 1a As shown, the Si@C / SiO obtained in Example 1 x It presents a morphology of small particles assembled into large spheres with a diameter of 5 to 20 μm. Compared with nano-silicon, the density has been greatly improved. This is the result of interface collision "welding" between particles under ball milling.
[0037] Figure 1b The Si@C / SiO obtained in Example 1 x Linear scanning diagram of elements in Si@C / SiO x At the shell layer, the peaks of carbon and oxygen elements are almost synchronously enhanced, indicating that Si@C / SiO x The shell layer is composed of C phase and SiO x Alternating structures.
[0038] Comparative Example 1
[0039] Chitosan is used as a carbon source material to prepare a carbon-coated lithium battery negative electrode material. The preparation method comprises the following steps:
[0040] (1) Add 60 mg of chitosan to 30 mL of 5% dilute acetic acid solution and stir in a 50°C water bath for 5 hours to obtain a concentration of 2 mg mL -1 Chitosan solution;
[0041] (2) adding 200 mg of nano-silicon to 10 mL of the chitosan solution obtained in step (1), stirring in a 70° C. water bath until the solvent is completely evaporated, and then drying in a vacuum oven at 100° C. for 24 h to obtain chitosan-coated nano-silicon;
[0042] (3) The sample obtained in step (2) is placed in a nitrogen atmosphere and carbonized at 900° C. for 2 hours to obtain a carbon-coated lithium battery negative electrode material Si@C.
[0043] Example 2
[0044] Using pitch as carbon source material to prepare C / SiO x The preparation method of the composite shell-coated lithium battery negative electrode material comprises the following steps:
[0045] (1) Add 60 mg of asphalt to 30 mL of tetrahydrofuran and stir in a 50°C water bath for 5 hours to obtain a concentration of 2 mg mL -1 Asphalt solution;
[0046] (2) adding 200 mg of nano-silicon to 10 mL of the asphalt solution obtained in step (1), stirring in a 60° C. water bath until the solvent is completely volatilized, and then drying in a vacuum oven at 100° C. for 24 h to obtain asphalt-coated nano-silicon;
[0047] (3) mechanically ball milling the asphalt-coated nano-silicon obtained in step (2) at a rotation speed of 450 rpm for 2 h;
[0048] (4) The sample obtained in step (3) was placed in a nitrogen atmosphere and carbonized at 800°C for 2 hours to obtain C / SiO x Composite shell-coated lithium battery anode material Si@C / SiO x .
[0049] Comparative Example 2
[0050] A carbon-coated lithium battery negative electrode material is prepared using asphalt as a carbon source material. The preparation method comprises the following steps:
[0051] (1) Add 60 mg of asphalt to 30 mL of tetrahydrofuran and stir in a 50°C water bath for 5 hours to obtain a concentration of 2 mg mL -1 Asphalt solution;
[0052] (2) adding 200 mg of nano-silicon to 10 mL of the asphalt solution obtained in step (1), stirring in a 60° C. water bath until the solvent is completely volatilized, and then drying in a vacuum oven at 100° C. for 24 h to obtain asphalt-coated nano-silicon;
[0053] (3) The sample obtained in step (2) is placed in a nitrogen atmosphere and carbonized at 800° C. for 2 hours to obtain a carbon-coated lithium battery negative electrode material Si@C.
[0054] The lithium battery negative electrode materials in Examples 1-2 and Comparative Examples 1-2 were respectively used to prepare working electrodes in a mass ratio of negative electrode material: acetylene black: sodium alginate = 6:2:2. The metal lithium sheet was used as the reference electrode. The button half-cells were assembled in a glove box and the electrochemical cycle performance was tested. The test results are shown in Tables 1 and Figure 2 shown.
[0055] Table 1 Comparison of electrochemical cycling performance results
[0056]
[0057] Depend on Figure 2 It can be seen that after 300 charge and discharge cycles at 1 A / g, the capacity of the button half-cell in Example 1 is still as high as 1721.2 mAh g -1 , the capacity retention rate is as high as 72.6%, while the capacity retention rate of the button half-battery in comparative example 1 is only 29.4% after 300 charge and discharge cycles.
[0058] By studying the X-ray photoelectron spectroscopy of the electrodes after different cycles, it can be found that for Example 1, after 5 electrochemical cycles, the main component of the SEI film is LiF with high lithium ion conductivity, and its content remains stable during the electrochemical cycle, indicating that SiO x The introduction of phase not only improves the C / SiO x The toughness of the composite shell avoids the breakage of the coating shell during the electrochemical cycle, maintains the stability of the SE I film on its surface, and realizes the regulation of the SE I film components. Figure 3a shown.
[0059] For comparative example 1, after 5 electrochemical cycles, the main component of the SE I film is Li x PO y F x / Li x PF y , accounting for as high as 59.3%, and with the increase of the number of cycles, Li x PO y F x / L i x PFy The proportion of SE I in the film continued to increase, reaching 70.6% after 100 cycles, as shown in Figure 3b As shown; this shows that for Comparative Example 1, side reactions continue to occur between Si and the electrolyte during the electrochemical reaction, and the SE I film continues to thicken, which in turn causes the continuous consumption of lithium ions in the battery and the rapid decay of capacity.
[0060] For additional notes on the background technology, see Table 2:
[0061] Table 2 C / SiO developed by the present invention x Composite shell and conventional carbon shell and oxide shell (TiO2, SiO x Comparison
[0062]
[0063] Technical features not described in the present invention can be achieved through or by adopting existing technologies and will not be described in detail here. Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by ordinary technicians in this technical field within the essential scope of the present invention should also fall within the scope of protection of the present invention.
Claims
1. A C / SiO x The composite shell-coated lithium battery negative electrode material is characterized in that: With silicon as the core and C / SiO x For composite shell, C / SiO x The composite shell is evenly coated on the silicon surface, and the C / SiO x C phase and SiO in the composite shell x Staggered arrangement.
2. A C / SiO according to claim 1 x The composite shell-coated lithium battery negative electrode material is characterized in that: Si@C / SiO x The morphology is that small particles are assembled into large spheres with a diameter of 5-20 μm.
3. A C / SiO x A method for preparing a lithium battery negative electrode material coated with a composite shell layer, used to prepare a C / SiO x The composite shell-coated lithium battery negative electrode material is characterized in that: The specific steps include: Step S1: uniformly dispersing the carbon source material in a solvent to obtain a carbon source material solution; Step S2: adding nano-silicon to the carbon source material solution obtained in step S1, stirring in a water bath until the solvent is completely volatilized, and then placing it in a vacuum oven to dry, to obtain nano-silicon coated with the carbon source material; Step S3: mechanically ball milling the nano-silicon coated with the carbon source material obtained in step S2; Step S4: The sample obtained after ball milling in step S3 is subjected to high temperature carbonization treatment under an inert atmosphere to obtain C / SiO x Composite shell-coated lithium battery negative electrode material, denoted as Si@C / SiO x .
4. A C / SiO according to claim 3 x A method for preparing a composite shell-coated lithium battery negative electrode material, characterized in that: In step S1, the carbon source material is one or a combination of chitosan, asphalt, and resin; The solvent is any one of deionized water, dilute acetic acid solution, methanol, ethanol, and N-methylpyrrolidone, or a combination of several of them; The dispersion method is any one of ultrasound, shear homogenization dispersion and mechanical stirring or a combination of these, and the concentration of the carbon source material solution is 0.5-10 mg mL -1 .
5. A C / SiO according to claim 3 x A method for preparing a composite shell-coated lithium battery negative electrode material, characterized in that: In step S2, the mass ratio of the nano-silicon to the carbon source material is 10:(0.1-5), the water bath temperature is 50-90°C, the temperature in the vacuum oven is 80-120°C, and the drying time is 5-30h.
6. A C / SiO according to claim 3 x A method for preparing a composite shell-coated lithium battery negative electrode material, characterized in that: In step S3, the mechanical ball milling parameters are: ball-to-material mass ratio is (8-12):1, ball mill speed is 200-1200rpm, and ball milling time is 2-24h.
7. A C / SiO according to claim 3 x A method for preparing a composite shell-coated lithium battery negative electrode material, characterized in that: In step S4, the protective atmosphere refers to any one of nitrogen and argon or a combination of them, and the high-temperature carbonization temperature range is 400-1600° C., and the high-temperature carbonization time is 0.5-10 h.